Textural and Structural Modification of Homo-Ionic Montmorillonite - Mervat S. Hassan (Adsorption Science & Technology)
The textural and structural modifications of calcium bentonite (CaB) induced by ion exchange, heat treatment and acid leaching were studied by infrared spectroscopy (IR), scanning electron microscopy (SEM) and nitrogen adsorption/desorption methods. The cation-exchange capacities (CEC) and the spontaneous and mechanical dispersion of the heat-treated samples were also measured. CaB taken from the northern coast of Egypt consisting of calcium montmorillonite (85%) and kaolinite, in addition to traces of quartz, was used in this study. CaB and its sodium and lithium forms, NaB and LiB, were calcined at 600 °C for times ranging from 2 h to 20 h, while selected calcined samples were leached with H 2 SO 4 for 1 h. Upon heating, the decrease in the layer charge caused by the fixation of Ca 2+ , Na + and Li + ions in the structure, as revealed by the CEC values, led to an upward shift of the Si–O stretching band in the IR spectrum to the frequency at which the Si–O groups of pyrophyllite absorb. The CEC values showed that the layer charge of the homo-ionic montmorillonite decreased with increasing thermal treatment time and that the amounts of fixed cations were in the order: Li + > Na + > Ca 2+ . The dispersability of the thermally-treated CaB was higher than that of NaB and LiB, both before and after mechanical dispersion. The high dispersability of CaB arises from the inability of the large Ca 2+ cation to penetrate further into the lattice. The textural parameters of heated samples showed that the zig-zag alignment of the silicate chains varied as a function of the heat-treatment time, irrespective of the nature of the exchangeable cations. A significant increase in the amount of pores with diameters in the range 13–38 Å was detected in the case of LiB. Heating LiB further for up to 20 h led to a slight increase in the specific surface area and pore volume, but with a considerable reduction in microporosity. On the other hand, thermal treatment after leaching led to a considerable increase in the specific surface areas, pore volumes and microporosities for those samples subjected to heating for a short time, but decreased progressively with increasing heating time, with no difference being observed to the exchangeable cations. This increase in surface area was mainly due to the presence of micropores whose formation was attributed to the leaching of octahedral cations. On the other hand, following calcination for a long time, the magnitude of the textural parameters diminished due to the gradual collapse of the microporous structure.